Sikap Toleransi Petani Dan Tingkat Adopsi Teknologi Usahatani Cabai Besar - Ratna Rahmatillah; Rahmaddiansyah Rahmaddiansyah; Anwar Deli (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Large chili (Capsicum annuum) is a horticultural plant (Family Solanaceae) that can adapt well and can be cultivated in almost all regions in Indonesia, including Aceh Province. The purpose of this study was to determine what technology was used by large chili farmers and to find out and analyze how the correlation between the tolerance level of large chili farmers and the level of technology adoption in Central Aceh and Bener Meriah districts. This study uses a descriptive crosstabulation method using 60 samples with a sampling technique in the form of quota sampling. The results showed that the tolerance attitude of large chili farmers who used technology in the districts of Aceh Tengah and Bener Meriah was in the medium category, which was the courage to take risks and have general efforts in overcoming risks. The technologies applied by large chili farmers in Central Aceh and Bener Merah districts are the use of superior seeds, cultivation techniques that have followed the recommendations of extension workers, use of vegetable pesticides, integrated pest control using mulch, hand tractors, sprayers, rain shelters, and KTA. The level of tolerance with the level of technology adoption is negatively correlated.